Upaya Pencegahan Demam Berdarah Dengue Melalui Program Pengabdian Kepada Masyarakat di Tabing Banda Gadang, Padang - Dwi Happy Anggi Sari; Nindy Notrilauvia; Rahmadhani Fitri; Elsa Yuniarti; Salman Alfarisy; Najmi Syafani Zahra; Arya Satya Upangga (BALE LITERASI, 2026)
Dengue Hemorrhagic Fever (DHF) remains a major vector-borne disease that imposes a significant public health burden in Indonesia. Effective dengue control necessitates active community participation, which can be optimized by enhancing health literacy through educational initiatives. This community-based action research aimed to evaluate the effectiveness of health education in improving public knowledge, attitudes, and practices (KAP) regarding dengue prevention. The intervention was conducted among the Pemberdayaan Kesejahteraan Keluarga (PKK—Family Welfare Movement) group in Tabing Banda Gadang Village, Padang City, utilizing lecture methods and interactive discussions covering etiology, transmission mechanisms, risk factors, and preventive strategies. Program evaluation was measured using a one-group pretest-posttest design with a structured questionnaire. The analysis demonstrated significant improvements across all indicators post-intervention: knowledge increased from 64.5% to 93.0%, attitude from 65.5% to 92.5%, and practice from 48.5% to 89.0%. The highest increase was observed in the practice domain (40.5%), followed by knowledge (28.5%) and attitude (27.0%). These findings confirm that community-based health education is effective in transforming public understanding and fostering preventive behavior. Consequently, this community-centered educational approach holds potential as a sustainable promotive and preventive strategy within national dengue control programs.